Expert elicitation of seasonal abundance of North Atlantic right whales Eubalaena glacialis in the mid-Atlantic - C Oedekoven; E Fleishman; P Hamilton; JS Clark; RS Schick (Endangered Species Research, 2015)
North Atlantic right whales Eubalaena glacialis are among the most endangered of the large whales. Although protected since 1935, their abundance has remained low. Right whales occupy the Atlantic Ocean from southern Greenland and the Gulf of St. Lawrence south to Florida. The highly industrialized mid-Atlantic region is part of the right whales’ migratory corridor, and gaps in knowledge of their movements through this region have limited the ability to make informed decisions about management of the species. To help fill these gaps, we elicited estimates of the relative abundance of adult right whales in the mid-Atlantic during 4 months (each month representing each season) from 10 experts on right whale ecology and management. We elicited the minimum, maximum, and mode as the number of individuals in a hypothetical population of 100 right whales, and confidence estimates as percentages. For each month-sex combination, we merged the 10 experts’ answers into 1 distribution. The estimated modes of relative abundances of both sexes were highest in January and April (females: 29 and 59; males: 22 and 23) and lowest in July and October (females: 5 and 9; males: 3 and 5). In some cases, our elicitation results were consistent with the results of studies based on sightings data. However, these studies generally did not adjust for sampling effort, which was low and likely variable. Our results supplement the results of these studies and will increase the accuracy of priors in complementary Bayesian models of right whale abundances and movements through the mid-Atlantic.